Children’s literature in latin america: Gender identity in the education - De Leo, Daniela; Armenise, Gabriella (Revista Internacional de Culturas y Literaturas, 2022)
This essay explores the notion of gender identity as a dynamic process, modelled by socio-cultural relationships, in the context of education in Latin America. The historical construction of schooling in recent decades is discussed through some documents of UNESCO. As an example of gender inequality within educational proposals, some texts from children’s literature will be analysed to highlight the gender stereotypes that still exist in the editorial industry today.